2024
DOI: 10.1021/acs.est.3c09504
|View full text |Cite
|
Sign up to set email alerts
|

Improved Water Collection from Short-Term Fog on a Patterned Surface with Interconnected Microchannels

Yanjun Wang,
Yumeng Zhou,
Peng Han
et al.

Abstract: Fog harvesting is considered a promising freshwater collection strategy for overcoming water scarcity, because of its environmental friendliness and strong sustainability. Typically, fogging occurs briefly at night and in the early morning in most arid and semiarid regions. However, studies on water collection from short-term fog are scarce. Herein, we developed a patterned surface with highly hydrophilic interconnected microchannels on a superhydrophobic surface to improve droplet convergence driven by the Yo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…The primary method of active water collection involves fog collection, known for its effectiveness, simplicity, and cost-efficiency, making it particularly suitable for addressing water scarcity in semiarid and water-deficient regions . In recent years, researchers have focused on improving the efficiency of fog collection to promote better practical applications. Because of the efficiency of fog collection depending on the design and construction of the surface engineering, many studies have reported innovatively constructing superhydrophilic–superhydrophobic hybrid surfaces (SSHSs) on the metal surface to improve fog collection efficiency inspired by the desert beetle. For instance, Liu et al constructed a hydrophilic–superhydrophobic hybrid surface on stainless steel using chemical etching and mechanical hole drilling to enhance fog collection efficiency .…”
Section: Introductionmentioning
confidence: 99%
“…The primary method of active water collection involves fog collection, known for its effectiveness, simplicity, and cost-efficiency, making it particularly suitable for addressing water scarcity in semiarid and water-deficient regions . In recent years, researchers have focused on improving the efficiency of fog collection to promote better practical applications. Because of the efficiency of fog collection depending on the design and construction of the surface engineering, many studies have reported innovatively constructing superhydrophilic–superhydrophobic hybrid surfaces (SSHSs) on the metal surface to improve fog collection efficiency inspired by the desert beetle. For instance, Liu et al constructed a hydrophilic–superhydrophobic hybrid surface on stainless steel using chemical etching and mechanical hole drilling to enhance fog collection efficiency .…”
Section: Introductionmentioning
confidence: 99%